2023
DOI: 10.3390/ma16041507
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behaviors of Microwave-Assisted Pyrolysis Recycled Carbon Fiber-Reinforced Concrete with Early-Strength Cement

Abstract: This study aimed to investigate the mechanical performance of early-strength carbon fiber-reinforced concrete (ECFRC) by incorporating original carbon fiber (OCF), recycled carbon fiber (RCF), and sizing-removed carbon fiber (SCF). Compressive, flexural, and splitting tensile strength were tested under three fiber-to-cement weight ratios (5‰, 10‰, and 15‰). The RCF was produced from waste bicycle parts made of carbon fiber-reinforced polymer (CFRP) through microwave-assisted pyrolysis (MAP). The sizing-removed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Patrinou et al [45] concluded that the compressive strength of cement composites increased with an increase in RCF dosage. Li et al [54] demonstrated that concrete composite with 10% of RCF dosage exhibited better compressive strength compared to concrete composites with 5% and 15% of RCF dosages. Similarly, Mastali et al [53] have investigated the influence of RCF dosage on cement composites by adding 0.5%, 1%, 1.5%, and 2% of RCF volume to a cement composite.…”
Section: Effect Of Rcf On Properties Of Cement Compositesmentioning
confidence: 99%
See 3 more Smart Citations
“…Patrinou et al [45] concluded that the compressive strength of cement composites increased with an increase in RCF dosage. Li et al [54] demonstrated that concrete composite with 10% of RCF dosage exhibited better compressive strength compared to concrete composites with 5% and 15% of RCF dosages. Similarly, Mastali et al [53] have investigated the influence of RCF dosage on cement composites by adding 0.5%, 1%, 1.5%, and 2% of RCF volume to a cement composite.…”
Section: Effect Of Rcf On Properties Of Cement Compositesmentioning
confidence: 99%
“…Their study indicated that a further increase in the RCF dosage up to 2.5% regressed flexural strength because of the agglomeration of RCF [45]. Li et al [54] have investigated the flexural strength of early strength concrete by adding a 5%, 10%, and 15% dosage of RCF. Their investigation concluded that a 10% addition of RCF improved the flexural strength of cement composites.…”
Section: Flexural Strength Tensile Strength and Other Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of sizing on the surfaces of fibers can affect the mechanical behavior of fiber-reinforced composites. Cement matrix composite specimens with sizing-removed carbon fibers can attain higher compressive strengths compared to untreated carbon fiber cement matrix composite specimens [28][29][30]. The sizing-removed fibers can be easily dispersed in the cementitious composite, and the bonding between the fibers and the cement can be notably improved.…”
Section: Introductionmentioning
confidence: 99%